Analytical techniques for detection of adulteration in crude palm oil - Inthiram, Anand Kumar (2015)
In recent years, the demand and consumption for Crude Palm Oil (CPO) has gradually increased in world market. However, production to fulfill the rising demand is rather slow. The gap between demand and production thus lead to potential frauds or adulteration of the CPO. Therefore, we are investigating the possibility of using analytical techniques such as gas chromatograph (GC), high performance liquid chromatograph (HPLC), differential scanning calorimetric (DSC) and Fourier transform infrared (FTIR) spectroscopy to detect CPO adulteration with sludge oil (SO) and used vegetable oil (UVO/UVOA). Investigations conducted with individual fatty acids and triacylglycerol by GC and HPLC analysis, respectively showed that it was very difficult to distinguish between genuine CPO from adulterated CPO. However, combination of fatty acids and triacylglycerols with multivariate statistical analysis produced more promising results. With these techniques, contaminated CPO with adulterants between 2-5% was easily detected by principle component analysis (PCA) and cluster analysis (Dendrogram). DSC thermograms showed that detection of adulteration was difficult to be determined by using heating thermogramd due to the polymorphism of oils and fats. However, the profile of DSC cooling thermograms showed changes in peak intensity as the amount of adulterant concentrations varied in CPO. This provided a positive indication that detection of adulterants in CPO could be determined from the changes in peak intensity. In parallel, application of multivariate and regression analysis were able to identify adulterant contents as low as 2% accurately in CPO. FTIR spectroscopy was the last technique applied to detect SO and UVO/UVOA adulteration. FTIR techniques seems to be the least promising technique to detect adulteration of CPO. However adulteration with used vegetable oil containing animal fat (UVOA) was clearly highlighted and was able to be discriminated by cluster analysis Dendrogram at level of 2 % using FTIR spectra. Nevertheless, further study is required to improve the level of detection as well as accuracy for discriminating genuine CPO from the adulterated CPO.